Effect of live ammunition shooting from an automatic rifle on sense of hearing in proffesional military personnel - Živaljević, Zvonko M; Živić, Ljubica; Bukumirić, Zoran; Nikolić, Ivan; Vorkapić, Branko; Baletić, Nenad (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. A short-term high-intensity noise from a gunshot impulse that occurs when using infantry weapon, can result in onset of auditory symptoms such as tinnitus, impaired hearing or feeling of pressure in one or both ears. The aim of this study was to examine the effect of live ammunition shooting from an automatic rifle on the hearing sense in professional military personnel. The examination was done in correlation with the conditions of the common shooting practice procedure. Methods. The research has been conducted on 22 professional soldiers serving in the Serbian Military, during their regular peacetime training shooting from the automatic rifle AP 7.62 mm M70. The training was conducted on the formational shooting field “Bubanj Potok”. The written consent from all subjects was acquired. All subjects were submitted to medical examination prior and after the shooting session. The medical examination consisted of anamnesis, clinical otorhinolaryngological examination, audiometry and impedancemetry. All subjects filled out the following questionnaire forms: “The Questionnaire prior to shooting” and “The questionnaire after shooting.” Subjects who were incapable to undergo shooting practice, whether from psychological or physical reasons were excluded from this study. Results. After the assessment of received data from 22 subjects, the results were as followed: in 2 (9%) subjects hearing impairment was diagnosed. Tinnitus was registered in 5 (22.7%) patients. One (4.5%) patient reported the feeling of pressure in one ear. One of two cases of one ear hearing impairment was on the rifle holding side and second case was on opposite lateral side. In both cases, hearing loss was of sensorineural type of milder degree, with a scotoma at 4,000 Hz in one case up to 50 dB and the second up to 55 dB. Conclusion. Auditory effects of impulse noise that occurs when shooting from automatic rifles cause hearing impairment, tinnitus and a feeling of pressure in the ears. The practical significance of this study lies in prevention which includes the mandatory use of personal protective equipment and functional arrangement of the practice shooting field.